From On‐Target to Off‐Target Activity: Identification and Optimisation of Trypanosoma brucei GSK3 Inhibitors and Their Characterisation as Anti‐Trypanosoma brucei Drug Discovery Lead Molecules. Issue 7 (14th June 2013) - Woodland, Andrew; Grimaldi, Raffaella; Luksch, Torsten; Cleghorn, Laura A. T.; Ojo, Kayode K.; Van Voorhis, Wesley C.; Brenk, Ruth; Frearson, Julie A.; Gilbert, Ian H.; Wyatt, Paul G.
Abstract Human African trypanosomiasis (HAT) is a life‐threatening disease with approximately 30 000–40 000 new cases each year. Trypanosoma brucei protein kinase GSK3 short (TbGSK3) is required for parasite growth and survival. Herein we report a screen of a focused kinase library against T. brucei GSK3. From this we identified a series of several highly ligand‐efficient TbGSK3 inhibitors. Following the hit validation process, we optimised a series of diaminothiazoles, identifying low‐nanomolar inhibitors of TbGSK3 that are potent in vitro inhibitors of T. brucei proliferation. We show that the TbGSK3 pharmacophore overlaps with that of one or more additional molecular targets.